Culture-Mediated Factors and Self-Esteem in Fast Food Consumption among Young Nigerian Adults - Nwantu, Esau Nanfwang; Nwan, Panshak Moses; Shitery, Irmiya Bahndi; Agun, Lami Ayuba; Dastu, Richard Ringle; Dashe, Nanman Dindam (NIU Journal of Humanities, 2021)
Over the years, researchers have investigated different factors that influence consumers’ choice preferences and consumer decisions. Like such previous studies, this study was designed to examine the influence of cultural factors and consumer self-esteem on the consumption of fast foods among young adult consumers in Nigeria. One hundred and seventy-five respondents (108 males and 67 females) drawn from different departments and faculties of three Universities in Central Nigeria were used for the study. Age ranges of participants were 18 – 45 years. Majority of the participants (93.7%) were Christians, 5.2% were Muslims and 1.1% practice the African Traditional Religion (ATR). Forty-two point nine percent (42.9%) of the participants perceived that cultural factors have no significant influence on their choice preferences including their consumption preferences while 57.1% perceived that cultural factors have significant influence on their consumption preferences. Thirty-five point four percent (35.4%) exhibited low self-esteem while 64.6% exhibited high self-esteem, respectively. Three hypotheses were tested in the study and one was supported while two were not. The result showed a significant influence of cultural factors on the consumption of fast foods F (1, 171) = -9.17, P < 0.05; but indicated that a consumer’s self-esteem does not have significant influence on his/her preference for fast foods within the population that was studied F (1, 171) = 1.38, P > 0.05. The result further revealed that there is no significant interaction effects of culture and consumer self-esteem on increased chances of fast foods consumption by young adult Nigerians F (1, 171) = 2.43, P > 0.05. These results were discussed in line with the findings of the study and recommendations were made. Keywords: Culture-mediated factors, self-esteem, fast foods, Nigerians